THE PORTRAIT OF YUSUF IN ULUGBEK KHAMDAM’S NOVEL “BALANCE” (The Conference Hub, 2025)
This article reveals the social situation of society through the life of Yusuf, the main character of Ulugbek Khamdam’s novel “Balance”, the hero’s thoughts, and his efforts to survive.